2022
DOI: 10.35808/ijeba/758
|View full text |Cite
|
Sign up to set email alerts
|

Firm Performance Indicators as a Fundamental Analysis of Stocks and a Determinant of a Firm’s Operation

Abstract: Purpose: The aim is to analyze which financial instruments effectively determine firm performance as key indicators of business success and the fundamental analysis of stocks. Design/methodology/approach: The study analyzed firm performance using financial statements for 100 listed Thailand companies via 513 observations during the period 2016-2020, including the economic COVID-19 crisis. The methodology was divided into two stages, at identifying the relevant dimensions of financial tools and firm size on fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(49 reference statements)
0
2
0
1
Order By: Relevance
“…It measures stocks' market price relative to their per-share earnings, indicating whether a stock is overvalued or undervalued in the market. A low P/E ratio means a company is probably undervalued or the company is performing well in relation to its past outstanding performance, which is attractive to investors [9]. Moreover, it is shown that P/E is significantly negative indicators of firm performance by using the ordinary least square regression logarithm.…”
Section: Fig 2 Process Of Analyzing Firmmentioning
confidence: 98%
See 1 more Smart Citation
“…It measures stocks' market price relative to their per-share earnings, indicating whether a stock is overvalued or undervalued in the market. A low P/E ratio means a company is probably undervalued or the company is performing well in relation to its past outstanding performance, which is attractive to investors [9]. Moreover, it is shown that P/E is significantly negative indicators of firm performance by using the ordinary least square regression logarithm.…”
Section: Fig 2 Process Of Analyzing Firmmentioning
confidence: 98%
“…Moreover, it is shown that P/E is significantly negative indicators of firm performance by using the ordinary least square regression logarithm. Besides, there is a strong negative impact of P/E ratio on EPS and ROE, which means stock with lower P/E has higher EPS and ROE, the sign of worth-investing companies [9]. The formula of P/E is:…”
Section: Fig 2 Process Of Analyzing Firmmentioning
confidence: 99%
“…Salah satu rasio utama dalam menentukan profitabilitas bank adalah rasio return on equity (ROE) (Mishra & Pradhan, 2019). Rasio ROE juga digunakan sebagai pengukur kinerja dari perusahaan (Malina et al, 2020;Naknok, 2022) dengan menunjukan seberapa efisien sebuah perusahaan dalam utilisasi modal yang dimiliki perusahaan (Pointer & Khoi, 2019). Non-performing Loans (NPL) menjadi salah satu determinan untuk menentukan tingkat kredit bermasalah pada perusahaan perbankan (Nugroho et al, 2021) dan menjadi salah satu faktor yang mempengaruhi profitabilitas perbankan dengan hubungan yang negatif (Trofimov et al, 2018).…”
Section: Telaah Literaturunclassified